Parent material, weathering and heavy metal contamination in the surface soils from basin infill sediments in Elazig Industrial Area, Eastern Turkey - Akkoca, Dicle Bal; Yildirim, Ismail; Al-Juboury, Ali Ismail (Pergamon-Elsevier Science Ltd, 2024)
In this study, geochemical properties were investigated to constrain the provenance, weathering conditions and to evaluate distribution and potential sources of heavy metals in the surface soils from basin infill sediments in Elazig Industrial Area, Eastern Turkey. Soil samples contain clay minerals (smectite, chlorite and illite), feldspar, quartz, calcite and dolomite. Geochemical patterns of major, trace and rare earth elements in soil samples generally are consistent with those of host rocks. Ba, Cs, Rb, Th, Zr and U contents are less than amounts of Post Archean Australian Shale composition, may reveal that source rocks of soils in the study area are of mafic composition. The Eu/Eu*, Th/Sc, Zr/Sc ratios show that source rocks of the most of the studied soil samples are of basic source except samples from the waste area. Chemical index of alteration (CIA) indices observed in the samples suggest that their source rocks were low to moderately weathered. The levels of metals in soil collected from all the sampling sites was found to decreased in the order of: Mn > Zn > Ni > Cr > Cu > Co > Pb > Mo > Cd. Enrichment factors, coefficients of variation, correlation analysis and principal component analysis were determined that sources of elements in soils are classified into two general categories; they are either lithogenic (natural) or anthropogenic (human made). It is found that source of Mn, Cr, Mo, Cd are anthropogenic, whilst source of Cu and Co are entirely and Pb, Zn, Ni are predominately lithogenic and, they are affected by geochemical character of the source rocks.
Keywords: Soil; Provenance; Alteration degree; Enrichment factor; Variation coefficient; Eastern Turkey